The School Lunch Project Administration Under School in Ayutthaya Primary Educational Service Area Office 1 - Doungsuwan, Sirotorn; Techawattanasiridumrong, Wacharapatr (Mahachula Academic Journal, 2021)
The purposes of this research were to (1) study the administration of the School Lunch Program in schools under Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1 (2) study the states and problems of administration for the School Lunch Program in schools under Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1 (3) present the School Lunch Program in schools under Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1. The samples of this research were administrators from 30 schools and 123 teachers who take responsibilities in the School Lunch Program through the Krejcie and Morgan’s table. The two instruments used in collecting data were following: 1) for the teachers who take responsibilities in the School Lunch Program had the reliability 0.98 2) for the administrators had the reliability 0.94. The statistics used for data analysis were Percentage, Average and Standard Deviation. The results of the research found that (1) The results of the research were: 1) the administrators operate the School Lunch Program in schools under Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1 were highly ( = 4.44) (2) the teachers who take responsibilities in the School Lunch Program indicate the states and problems of administration for the School Lunch Program in schools under Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1 were low ( = 2.36) (3) the guidelines for developing the School Lunch Program in schools under Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1 were respectively following; section1 the administrator should plan the use of budget for the School Lunch Program. Section 2 the administrator should coordinate with Provincial Administrative Organizations. Section 3 the administrator should audit and monitor the School Lunch Program financial account evidently. Section 4 the administrator should support the teachers for developing themselves in the School Lunch Program.